New Insights in the Interplay Between African Swine Fever Virus and Innate Immunity and Its Impact on Viral Pathogenicity - Ayanwale, Abraham; Trapp, Sascha; Guabiraba, Rodrigo; Caballero, Ignacio; Roesch, Ferdinand (Frontiers in Microbiology, 2022)
The continuous spread of African Swine Fever Virus (ASFV) in Europe and Asia represents a major threat to livestock health, with billions of dollars of income loss and major perturbations of the global pig meat sector. One striking feature of African Swine Fever (ASF) is the existence of different forms of the disease, ranging from acute- with mortality rates approaching 100%- to chronic, with mild clinical manifestations. These differences in pathogenicity have been linked to genomic alterations present in attenuated ASFV strains (and absent in virulent ones) and differences in the immune response of infected animals. In this mini-review, we will summarize current knowledge on the connection between ASFV virulence and the innate immune response induced in infected hosts, with a particular focus on the pathways involved in ASFV detection. Indeed, recent work has highlighted the key role of cGAS, a pattern recognition receptor (PRR) involved in the detection of many DNA viruses, in ASFV sensing. We will discuss which other sensing pathways (beyond cGAS/STING) may be involved in ASFV sensing, and summarize recent findings on the viral ASFV genes involved in the modulation of the interferon (IFN) and NF-κB pathways.